Multidrug-Resistant Acinetobacter baumannii mediastinitis - Selman Dumani; Edmond Puca; Ermal Likaj; Stavri Llazo; Edlira Rruci; Vera Beca; Ali Refatllari; Arben Baboci (Journal of Infection in Developing Countries)
Introduction: Mediastinitis remains one of the most serious complications of cardiac surgery. The reported incidence is 1–4%, while the related mortality varies from 10–47%.